General practice (GP) level analysis shows that patients' own perceptions of support within primary care as reported in the GP patient survey (GPPS) are as important as medication and services in improving glycaemic control. Issue 1 (February 2020) - Heald, Adrian; Stedman, Mike; Lunt, Mark; Livingston, Mark; Cortes, Gabriela; Gadsby, Roger
Highlights: The way that multi-morbidity is addressed in primary care has an impact on outcome. We are seeing clustering of physical/mental health conditions in a single patient. We used independent data sets, GP practice patient survey and National Diabetes Audit. We showed a critical relation between the person with diabetes & clinician perception. This is as important in influencing glycaemia as the services provided/medication. Abstract: Background: The way that GP practices organize their services impacts as much on glycaemia in type 2 diabetes as does prescribing. Aim: Our aim was to evaluate the link between patients' own perception of support within primary care and the % patients at each GP practice at target glycaemic control (TGC) and at high glycaemic risk (HGR). Design and Setting: Utilisation of National Diabetes Audit (NDA) available data combined with the General practitioner patient survey (GPPS). Method: The NDA 2016_17 published data on numbers of type 2 patients, levels of local diabetes services and the target glycaemic control (TGC) % and high glycaemic risk (HGR) % achieved. The GPPS 2017 published % "No" responses from long term condition (LTC) patients to the question "In the last 6 months, had you enough support from local services or organisations to help manage LTCs?". Multivariate regression was used on the set of indicators capturing patients' demographics and services provided. Results: 6498 practices were included (with more than 2.5 million T2DM patients) and median values with band limits that included 95% practices for % "No" response to the question above was 12% (2%–30%), for TGC 67% (54%–78%) and for HGR 6% (2%–13%). The model accounted for 25% TGC variance and 26% HGR variance. The standardised β values shown as (TGC/HGR) (+=more people; −=less people) for older age (+0.24/−0.25), sulphonylurea use (−0.21/+0.14), greater social disadvantage (−0.09/+0.21), GPPS Support %No (−0.08/+0.12), %Completion 8 checks (+0.09/−0.12) and metformin use (+0.11/−0.05). Conclusion: The relation between the person with diabetes and clinician in primary care is shown to be quantitatively potentially as important in influencing glycaemic outcome as the services provided and medication prescribed. We suggest that all of us in who work in the health care system can bear this in mind in our everyday work.